The role of indigenous institutions in achieving the state defense program in West Sumatera to support the defense of the country - Abdur Rahim; Sutrimo Sumarlan; Wayan Nuriada (Strategi Perang Semesta, 2022)
The Province of West Sumatera has Minangkabau Customary Institutions, namely 19 LKAAM (Minangkabau wide Association of Village Adat Council) at the regency/city level, 179 LKAAM at the district level, and 1274 KAN at the nagari (village level) with a population of 580,232. The partnership between the LKAAM and the West Sumatera government accommodates the distribution of aspirations of indigenous communities in terms of preserving indigenous values in the community. LKAAM has a purpose in preserving Minangkabau customs and culture, to the next generation by institutionalizing and increasing community participation, to succeed regional development within the framework of national development altogether. The authors will discuss the role of indigenous institutions in achieving the state defense programs in West Sumatera to support the state defense. This following article utilize library research as the research method, obtained from various literature sources. Based on the result of the discussion, it shows that the existence of LKAAM as an indigenous institution has a strategic role in realizing a developed and independent Minangkabau community, depicting the philosophical nuances of "Adat basandi Syara' and Syara'basandi kitabullah". The local government reaps the benefits and functions of LKAAM, in accelerating regional development, especially in achieving state defense programs.